(untitled) (Polis (Santiago), 2022)
This article analyzes police violence against sexual dissidents happened during the protests that began on October 18, 2019, in Chile, through three police cases whose reports reveal testimonies and the subsequent actions that involved activists and academics. From a decolonial perspective, this article expands content and reflections on such reports, highlighting their production process and their practical scope with respect to epistemic justice. This study affirms, in its conclusions, that violence against sexual dissidents was supported by racism, revealing its role as a pivot for the reproduction of epistemic injustice.